Sustainable Coastal Tourism Berbasis Kearifan Lokal Di Kawasan Rekreasi Pantai Terbuka Kota Denpasar - Sastrawan, I Gede Anom; Ariwangsa, I Made Bayu; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA, 2022)
This study aims to describe the potential of coastal tourism at the Open Beach of Denpasar City. Denpasar City is administratively divided into 4 sub-districts from west to east, namely West Denpasar District, East Denpasar District, North Denpasar District, and South Denpasar District. One of the coastal tourism in Denpasar City is located in the Open Beach Recreation Area which stretches on the coast of Sanur Kaja Village to Sanur Kauh Village, where the Sanur village community has managed natural resources by paying attention to environmental balance and harmony. This study applies the Principles of Sustainable Coastal Tourism which are described as follows: 1. The Principle of Balance Tourism management must be based on a commitment to a balanced pattern between economic development, socioculture, and conservation, 2. The Principle of Community Participation Involving the community in the management of tourism businesses, 3. Principles of Conservation Have concern, responsibility, and commitment to environmental conservation (nature and culture), 4. Principles of Integrated Management pay attention to ecosystem conditions and synergize with the development of various sectors, 5. Principles of Law Enforcement Tourism management must be developed following applicable regulations. The analytical technique used in this study is an analytical technique using a qualitative descriptive approach to determining the informants in this study, the researchers chose the snowball sampling technique, which is the direction used by the researcher where when the researcher does not know much about the research population, it is expected to provide an overview and analysis of the policy. the government in government policies related to the development of coastal tourism based on local wisdom in the Denpasar City Open Beach Recreation Area Keyword: Coastal Tourism, Potential, Tourism, Principles of Sustainable